The Photocatalytic Activity of TiO2 Nanotube Doped Zn for Methylene Blue Degradation - Nursanto, Eduardus Budi; Floresyona, Dita; Hadi, Abdul (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
TiO2 nanotube (TiO2-NT) is one of the promising materials for photocatalytic water remediation. TiO2-NT doped Zn (Zn/TiO2-NT) is synthesized from P25 Degussa via one step hydrothermal method. From XRD and UV-DRS analysis, it showed that Zn as a doping material led to decrease band gap energy and decrease the crystallite size. The best results obtained was Zn/TiO2-NT with a crystallite size of 7.14 nm, and band gap energy value of 3.18 eV. Photocatalytic activity of Zn/TiO2-NT was also tested for photocatalytic activity of textile dye (methylene blue) degradation. During the photocatalytic activity for methylene blue degradation, the Zn/TiO2-NT shows higher activity compared to non-doped sample. The non-doped sample shows degradation activity of 87.72%, meanwhile the Zn/TiO2-NT shows degradation activity of 95.88%.